A blockchain‐based privacy‐preserving authentication system for ensuring multimedia content integrity. Issue 5 (28th January 2022) - Li, Xudong; Wei, Lingbo; Wang, Lidong; Ma, Ying; Zhang, Chi; Sohail, Muhammad
Abstract: With the prevalence of digital cameras, multimedia data have been used to record facts and provide evidence of events. However, the integrity of multimedia data is vulnerable to attacks with the proliferation of data tampering tools. In fact, an effective multimedia content authentication system should support compliant editing (cropping, rotation, compression, and so forth) and have the ability to detect malicious data tampering. Data traceability is a feasible strategy to verify the integrity and provenance of multimedia data. Besides, the privacy of multimedia data needs to be protected to prevent unauthorized access. In this paper, we trace transformations of multimedia data privately by integrating a transparent and immutable blockchain with trusted hardware that provides the capability of private computation. Our system exploits a hybrid storage pattern that separately stores multimedia data off the blockchain and their hashes on the blockchain. With this, our system ensures data integrity and addresses the issue of blockchain's storage capability. Experimental results and analysis show that our solution is efficient and verifiable. A lightweight verifier merely needs to store block headers and is able to validate query results returned by full nodes.